Mass spectrometry studies of lycodine-type Lycopodium alkaloids: sauroxine and N-demethylsauroxine - Cifuente, Diego Alberto (2014)
RATIONALE: Sauroxine and N-demethylsauroxine are lycodine-type Lycopodium alkaloids. In recent years, Lycopodium alkaloids have gained significant interest due to their unique skeletal characteristics as well as due to their acetylcholinesterase activity. It is known that drugs that inhibit acetylcholinesterase can be used to treat the early stages of Alzheimer’s disease. METHODS: Sauroxine and N-demethylsauroxine were isolated from the aerial parts of Huperzia saururus (Lam.) Trevis. Electron ionization mass spectrometry (EI-MS) (low resolution) and collision-induced dissociation tandem mass spectrometry (CID-MS/MS) fragmentation was conducted using an ion trap, GCQ Plus mass spectrometer with MS/MS. Electron ionization high-resolution mass spectrometry (EI-HRMS) was performed in a magnetic sector mass spectrometer (Micromass VG). RESULTS: Using GC/EI-CID-MS/MS we obtained different fragmentation routes that connect all the ionic populations. In addition, the use of EI-HRMS allowed us to measure the exact masses of all the fragment ions, and, with all this information gathered, we tried to establish a fragmentation scheme concordant with the ascendant and descendant species. CONCLUSIONS: The mass spectrometry studies presented in this work complete our mass studies of Lycopodium alkaloids. The mass spectrometry work presented has been very useful to confirm the structures as well as to support the biogenetic relationships between the lycodine-type Lycopodium alkaloids: sauroxine and N-demethylsauroxine